Childhood Convulsion: Inquiry about the Concerns and Home Management among Mothers in Tegbesun, a Periurban Community in Ilorin, Nigeria. (20th November 2012) - Anigilaje, Emmanuel Ademola; Anigilaje, Omolara Olufunmilayo
Abstract : Background . The fear and panic felt by most parents when their child convulsed made them apply all sorts of management. Objective . This study evaluated the concerns and home management of childhood convulsions among mothers in Tegbesun, a periurban community in Ilorin, Nigeria. Methods . A ten-week cross-sectional study comprising 500 mothers interviewed using a structured questionnaire. Results . Fear of death was the commonest concern (450, 90%) among mothers. For a witnessed convulsion, the majority took the child to the hospital (414, 82.8%). Cow's urine concoction (74, 87.1%) was the most common item administered to a convulsing child. Putting the hand and/or a spoon into the mouth of the convulsing child was the commonest unwholesome practice (74, 61.2%). None of the subjects safely put the convulsing child on his/her side. Conclusions . Maternal concerns are precursors of mismanagement of childhood convulsions, and health education was undertaken at the end of the study.